Melatonin supplementation may improve the outcome of patients with hemorrhagic stroke in the intensive care unit - Mehrnoush Dianatkhah; Atabak Najafi; Mohammad Sharifzadeh; Arezoo Ahmadi; Hamidreza Sharifnia; Mojtaba Mojtahedzadeh; Farhad Najmeddin; Azadeh Moghaddas (Wolters Kluwer Medknow Publications, 2017)
Objective: Although mechanical ventilation is frequently a life-saving therapy, its use can result in unwanted side effects. It has been well documented that the choice of sedating agent may influence the duration of mechanical ventilation. Melatonin is a sedative and analgesic agent without any respiratory depressant effect which makes it an attractive adjuvant for sedation in the intubated patients. The aim of this study is to evaluate the effect of melatonin on the duration of mechanical ventilation in patients with hemorrhagic stroke. Methods: Forty adult intubated patients with hemorrhagic stroke, who were admitted to the Intensive Care Unit (ICU) within 24 h of onset, were enrolled in this randomized double-blind study. Subjects in the melatonin group received 30 mg of melatonin every night throughout the nasogastric tube. Length of ICU stay, mortality, and duration of mechanical ventilation were recorded for all patients. Findings: The duration of mechanical ventilation and length of ICU stay were shorter in patients who received melatonin in comparison with the control group, and this difference was statistically significant for the length of ICU stay and marginally significant for the duration of mechanical ventilation. Although not statistically significant, the mortality rate of the control group was 30%, almost double that of the study group (15%). Conclusion: Melatonin possesses hypnotic, analgesic, anti-inflammatory, and anti-oxidative properties that distinguish it as an attractive adjuvant in patients under mechanical ventilation. In conclusion, the administration of melatonin may facilitate the weaning process through decreasing the consumption of sedatives with respiratory depressant properties as well as preventing ventilator-associated lung injury.